Self-report fatigue questionnaires in multiple sclerosis, Parkinson’s disease and stroke: a systematic review of measurement properties - Elbers, Roy G. (Springer Netherlands, 2011)
PURPOSE: To critically appraise, compare and summarize the measurement properties of self-report fatigue questionnaires validated in patients with multiple sclerosis (MS), Parkinson’s disease (PD) or stroke. METHODS: MEDLINE, EMBASE, PsycINFO, CINAHL and SPORTdiscus were searched. The COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) checklist was used to assess the methodological quality of studies. A qualitative data synthesis was performed to rate the measurement properties for each questionnaire. RESULTS: Thirty-eight studies out of 5,336 records met the inclusion criteria, evaluating 31 questionnaires. Moderate evidence was found for adequate internal consistency and structural validity of the Fatigue Scale for Motor and Cognitive functions (FSMC) and for adequate reliability and structural validity of the Unidimensional Fatigue Impact Scale (U-FIS) in MS. CONCLUSIONS: We recommend the FSMC and U-FIS in MS. The Functional Assessment of Chronic Illness Therapy Fatigue subscale (FACIT-F) and Fatigue Severity Scale (FSS) show promise in PD, and the Profile of Mood States Fatigue subscale (POMS-F) for stroke. Future studies should focus on measurement error, responsiveness and interpretability. Studies should also put emphasis on providing input for the theoretical construct of fatigue, allowing the development of questionnaires that reflect generic and disease-specific symptoms of fatigue. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11136-011-0009-2) contains supplementary material, which is available to authorized users.